Are indexing and documentary languages knowledge organization systems? A Bardian analysis of terminological variation - Lopes Fujita, Mariangela Spotti [UNESP]; Piovezan dos Santos, Luciana Beatriz [UNESP]; Alves, Roberta Vesu [UNESP] (Univ Zaragoza, 2018)
In the Knowledge Organization field, the terms indexing languages, documentary languages and knowledge organization systems are generally considered without a terminological distinction. The hypothesis about a possible shared conceptual evolution between these terms was verified, through the methodology of Bard in's content analysis, in recent events of the International Society of Knowledge Organization. It was shown that the term Knowledge Organization Systems can be considered a terminological variation of the terms Indexing Language and Documentary Language, although it also refers to the organization and retrieval of information in the digital environment and the semantic web, being considered as a new denomination for representation and retrieval tools in this environment.
Keywords: Indexing languages; Documentary languages; Knowledge organization systems; Terminological variations; Terminology